Pseudomyxoma peritonei - Suárez-Torres, Ismael (2017)
Pseudomyxoma peritonei is a relatively rare and poorly understood condition in which mucin accumulates within the peritoneal cavity. Classically, it is characterized by diffuse intra-abdominal gelatinous collections (“jelly belly”) with mucinous implants on peritoneal surfaces. A case of pseudomyxoma peritonei originated from a mucinous cystadenoma of the ovary is presented in a 56-year-old woman with history of hypogastric pain and abdominal distension, nausea and vomiting. Pelvic ultrasound scan revealed a solid-cystic echogenic mass arising from the right adnexa and free fluid of mixed echogenicity in the abdomen. Gynecological laparotomy, aspiration of mucinous fluid and hysterectomy were performed revealing mucinous cystadenoma of the ovary and mucoid peritoneal fluid compatible with pseudomyxoma peritonei.